The Effect of Difference In Press Time on Physical Properties and Mechanical Particle Board Without Adhesive From Coconut Fiber and Gambier Processed Pulp - Sahadi Sahadi; Neswati Neswati; Ananda Agung Perkasa (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
This study aims to determine the effect of differences in the length of time when pressing for the manufacture of particle board without adhesive from a mixture of coconut coir fiber and processed gambir leaf dregs on the physical and mechanical properties of the resulting non-adhesive particle board. The method used in this study was a completely randomized design with 5 treatments and 3 replications. Data were analyzed using variance, followed by Duncan`s New Multiple Range Test (DNMRT) at 5% level. The comparison ratio used in the manufacture of particle board without adhesive from coconut coir fiber and processed gambir waste is 60% : 40%. The treatments in this study were A (8 minutes of pressing time), B (10 minutes of pressing time), C (12 minutes of pressing time), D (14 minutes of pressing time), E (16 minutes of pressing time). carried out is a test of physical properties and mechanical properties. The results showed that the length of time of compression affected the physical and mechanical properties of the non-adhesive particleboard. The best treatment was treatment A (pressing time 8 minutes). Observation of physical properties obtained density 0.68 g/cm3, moisture content 13.42%, water absorption 132.87%, thickness swelling 66.84%, mechanical properties fracture toughness (MOR) 90.40 kg/cm2, toughness compressive parallel to the surface of 50.07 kg/cm2, and internal bond (IB) 1.45 kg/cm2.